p+(-3p+6)=4a(-5p+3)-10p

Simple and best practice solution for p+(-3p+6)=4a(-5p+3)-10p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p+(-3p+6)=4a(-5p+3)-10p equation:


Simplifying
p + (-3p + 6) = 4a(-5p + 3) + -10p

Reorder the terms:
p + (6 + -3p) = 4a(-5p + 3) + -10p

Remove parenthesis around (6 + -3p)
p + 6 + -3p = 4a(-5p + 3) + -10p

Reorder the terms:
6 + p + -3p = 4a(-5p + 3) + -10p

Combine like terms: p + -3p = -2p
6 + -2p = 4a(-5p + 3) + -10p

Reorder the terms:
6 + -2p = 4a(3 + -5p) + -10p
6 + -2p = (3 * 4a + -5p * 4a) + -10p
6 + -2p = (12a + -20ap) + -10p

Solving
6 + -2p = 12a + -20ap + -10p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '20ap' to each side of the equation.
6 + 20ap + -2p = 12a + -20ap + 20ap + -10p

Combine like terms: -20ap + 20ap = 0
6 + 20ap + -2p = 12a + 0 + -10p
6 + 20ap + -2p = 12a + -10p

Add '10p' to each side of the equation.
6 + 20ap + -2p + 10p = 12a + -10p + 10p

Combine like terms: -2p + 10p = 8p
6 + 20ap + 8p = 12a + -10p + 10p

Combine like terms: -10p + 10p = 0
6 + 20ap + 8p = 12a + 0
6 + 20ap + 8p = 12a

Add '-6' to each side of the equation.
6 + 20ap + -6 + 8p = -6 + 12a

Reorder the terms:
6 + -6 + 20ap + 8p = -6 + 12a

Combine like terms: 6 + -6 = 0
0 + 20ap + 8p = -6 + 12a
20ap + 8p = -6 + 12a

Reorder the terms:
6 + -12a + 20ap + 8p = -6 + 12a + 6 + -12a

Reorder the terms:
6 + -12a + 20ap + 8p = -6 + 6 + 12a + -12a

Combine like terms: -6 + 6 = 0
6 + -12a + 20ap + 8p = 0 + 12a + -12a
6 + -12a + 20ap + 8p = 12a + -12a

Combine like terms: 12a + -12a = 0
6 + -12a + 20ap + 8p = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(3 + -6a + 10ap + 4p) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(3 + -6a + 10ap + 4p)' equal to zero and attempt to solve: Simplifying 3 + -6a + 10ap + 4p = 0 Solving 3 + -6a + 10ap + 4p = 0 Move all terms containing p to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -6a + 10ap + -3 + 4p = 0 + -3 Reorder the terms: 3 + -3 + -6a + 10ap + 4p = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -6a + 10ap + 4p = 0 + -3 -6a + 10ap + 4p = 0 + -3 Combine like terms: 0 + -3 = -3 -6a + 10ap + 4p = -3 Add '6a' to each side of the equation. -6a + 10ap + 6a + 4p = -3 + 6a Reorder the terms: -6a + 6a + 10ap + 4p = -3 + 6a Combine like terms: -6a + 6a = 0 0 + 10ap + 4p = -3 + 6a 10ap + 4p = -3 + 6a The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 9=12x-6-7x | | n^2-2n=11 | | x^(2/3)=9 | | Y=sin(16x) | | x+2x=45600 | | F(x)=3/4x-5 | | ln(x+3)+ln(x+5)=0 | | 4m+4m-8m+m=9 | | .3a=14 | | 5-3(2X-4)=29 | | 2y+13= | | (1/2)(sqr3/2) | | 8x^4+16x^3-12x^2+4x= | | D=10+7 | | 2(sqr3/2) | | 8w^2=32 | | 14h-3h+-17h=18 | | 5m^2=125 | | -7(1-8a)+5a=-7+5a | | 8x-6+5x+12=180 | | 7y-2(3-1)=8 | | 28-8x=-1211x | | 2n+3.6=6.4whatisn | | ln(x^2+4x-5)-ln(x+5)=1 | | (8-x)+(3-x)=11 | | 5t^4-25t^2-20=0 | | 9x-2=10x-9 | | 127+2x+41=180 | | 5t^2-25t+20=0 | | (69.8+x)/7=70 | | 6n+3.30=7.80 | | a=4+1.5y |

Equations solver categories